Job Burnout on Subjective Well-Being Among Chinese Female Doctors: The Moderating Role of Perceived Social Support - Wang, Liping; Wang, Huiping; Shao, Shuhong; Jia, Gaizhen; Xiang, Jing (Frontiers in Psychology, 2020)
Doctors face the challenges and pressures of job burnout. The dual pressures of work and family make female doctors more likely to feel burnout and less happy, but few studies have focused on female doctors. We conducted the study to explore the influence of job burnout on female clinical doctors’ subjective wellbeing, and the moderating role of perceived social support. Casual Comparative study design was used for this research. Three self-reported scales (Maslach Burnout Inventory, Perceived Social Support Scale and Subjective Wellbeing Scale) were distributed; Random sampling selection was conducted to select participants. Both 120 female and male doctors from a hospital of Yantai City were selected and analyzed for comparison. The female doctors in the emotional exhaustion dimension were significantly higher than that of male doctors (p＜0.01), subjective wellbeing was comparatively lower than that of male doctors (p＜0.01). The three dimensions of job burnout and subjective wellbeing had significant negative correlations and there was a positive relationship between perceived social support and subjective wellbeing in female doctors (p＜0.01). Regression results showed that subjective wellbeing was predicted by emotional exhaustion, depersonalization, low personal accomplishment, and perceived social support. Perceived social support played a moderating role between job burnout and subjective wellbeing, especially family support, the moderating effect was significant (p＜0.01). A significant difference was observed between male and female doctors. It had shown that female doctors had more emotional exhaustion and lower subjective wellbeing than the males. Job burnout and subjective wellbeing had significant negative correlations, family support played a moderator role. Improving perceived social support could reduce burnout, enhance subjective wellbeing.